Development of a Human IFN-β Expression System using Chinese Hamster Ovarian Cells - Hylton, Todd Cameron (East Carolina University, 2019)
Two human IFN-β expression systems were derived based on the pIRES2-AcGFP1 plasmid backbone. One expression plasmid encoded human IFN-β fused to a C-terminal linker and an 8-histidine affinity chromatography tag. A second expression plasmid encoded human IFN-β without the C-terminal additions to determine if the addition of the 8-his tag alters IFN-β function. Both expression vectors encoded the native signal sequence to direct secretion of IFN-β as a glycosylated soluble protein. These plasmids were then transfected into Chinese Hamster Ovary (CHO) cells. Stable transfected CHO cells were selected based on plasmid-encoded resistance to the antibiotic Geneticin. IFN-β-producing cells were selected by Fluorescence-Activated Cell Sorting of the brightest 10% fraction of GFP+ cells. Expression supernatants from each cell line exhibited similar amounts of cytotoxic activity in the IFN-β reactive TF-1 erythroleukemia cell line. These results provided suggestive evidence that the C-terminal affinity tag did not adversely affect the activity of the N-terminal IFN-β cytokine domain. This IFN-β-8his recombinant protein was purified by Ni-NTA affinity chromatography and was shown to exhibit potent activity in the in vitro TF-1 cytotoxicity assay. Human peripheral blood mononuclear cells (PBMCs) were activated with Con-A, IL-2, and either IFN-β, TGF-β, IFN-β + TGF-β, or no additional cytokine. Cell numbers were counted at each passage. The main finding was that IFN-β caused the induction of T cell anergy. Human T cells (90% CD8+) were activated with RS4 (11) cells (acute lymphoblastic leukemia cell line), Con-A, and IL-2 in the presence or absence of IFN-β, TGF-β, IFN-β + TGF-β. T cells were cultured for eight days, and then reactivated. Supernatants were collected from reactivation cultures to measure IL-2 production as a measure of T cell responsiveness. Human T cells activated in the presence of IFN-β and TGF-β produced less IL-2 compared to T cells activated in the absence of TGF-β alone. This expression system will be used to reveal whether IFN-β elicits differentiation of human FOXP3+ Tregs.
Keywords: Multiple Sclerosis, IFN-β, expression system